Comparison on the Efficacy between Partially Covered Self-Expandable Metal Stent with Funnel-Shaped Enlarged Head versus Uncovered Self-Expandable Metal Stent for Palliation of Gastric Outlet Obstruction - Jung Wan Choe; Jong Jin Hyun; Dong-won Lee; Sang Jun Suh; Seung Young Kim; Sung Woo Jung; Young Kul Jung; Ja Seol Koo; Hyung Joon Yim; Sang Woo Lee (Gastroenterology Research and Practice)
Background. Shape modification has been one of the methods adopted to improve stent patency but has not always translated into positive outcome. The aim of this study was to compare the efficacy of shape-modified partially covered self-expandable metal stent (SEMS) that has enlarged head versus uncovered SEMS for palliation of gastric outlet obstruction (GOO). Methods. A total of 48 patients underwent insertion of either enlarged-head SEMS (n=24) or uncovered SEMS (uSEMS) (n=24) for palliation of GOO from July 2009 to July 2016. Patients with inoperable or advanced malignancy were included. Technical feasibility and clinical outcomes were compared. Results. Technical success rate was 100% (24/24) and 95.8% (23/24) for enlarged-head SEMS group and uSEMS group, respectively. Clinical success rate was 87.5% (21/24) and 87.0% (20/23) for enlarged-head SEMS group and uSEMS group, respectively. The gastric outlet obstruction scoring system score significantly improved in both groups (p<0.001 for both). Mean survival was similar between the groups: enlarged-head SEMS group, 99.3 days (range, 19–358 days) versus uSEMS group, 82.1 days (range, 11–231 days) (p=0.418). The mean stent patency also showed no difference between the groups: enlarged-head SEMS group, 87.1 days (range, 8–358 days) versus uSEMS group, 60.4 days (range, 2–231 days) (p=0.204). With enlarged-head SEMS, distal migration did not occur, but proximal migration was observed in four cases. Conclusions. Distal migration was prevented by shaping the SEMS to have an enlarged head, but improvement in stent patency could not be observed.